Sosialisasi Literasi Digital dan Keamanan Data untuk Pelaku Usaha Mikro, Kecil, dan Menengah di Desa Sei Rejo - Daniel Collyn; Rapat Piter Sony Hutauruk; Suci Etri Jayanti S; Murbanto Sinaga; Rika Surianto Zalukhu; Suwadi Suwadi; Ayu Zurlaini Damanik; Yenni Mariani Sinurat; Sri Winda Hardiyanti Damanik; Bobby Hartanto; Kumala Vera Dewi; Cici Puspaningrum; Donald Frensius Pasaribu (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
MSME actors in Sei Rejo Village face infrastructure limitations, low access to digital training, and a lack of guidance, which result in inadequate levels of digital literacy. These challenges prompted the service team to carry out a community engagement activity for MSMEs in Sei Rejo Village, Sei Rampah Sub-district, Serdang Bedagai Regency, to promote awareness of digital literacy and data security. The activity was conducted in the form of a socialization session aimed at improving entrepreneurs’ understanding of the importance of digital literacy and data protection. The session was attended by 20 participants. This community engagement was implemented using a participatory approach through socialization, training, and mentoring methods. The stages of the activity included preparation, implementation, and assistance. This initiative had a positive impact on MSME actors in Sei Rejo Village. The training not only provided conceptual understanding but also practical skills, such as the use of social media for promotion, utilization of cashier applications and digital wallets, and techniques for personal data protection. It also broadened participants' insights on the importance of building consumer trust through secure and professional information management.